Culture of private heritage in the state of Tabasco (Revista de Investigaciones Universidad del Quindío, 2021)
The scarce culture of private heritage is one of the circumstances that originate conflict between individuals that end in long litigation in the Courts.In addition to the scarce public policies for their protection, it has been the propitious field for pseudo real estate managers to abuse people who in good faith put in their hands the heritage that with a lifetime of effort they have built.The culture of private heritage is important for the quality of life of people and for a company it is essential to survive and continue contributing to the economic activation and generation of jobs.That is why, at the time of carrying out any transaction on people's private assets, at least they must be informed of what the basic provisions are to carry out their legal act and that they have certainty of the property they acquire, and avoid future problems.
Keywords: Culture; Private equity; Accession; Award; Succession; Usucaption or positive prescription; Occupation; Contract; The law